Blue Ocean Leadership (BOL) practices towards promoting employee engagement in public service - Zakaria, Zaki; Idris, Khairuddin; Ismail, Mohd Bakhari (Human Resource Management Academic Research Society, 2017)
Malaysia has bold intention to be an advanced nation in 2020. Here, public service holds the key as they are the primary facilitator in achieving this noble dream. It required fully engaged public service workforce as achieving Vision 2020 is an ardours task. Getting employees’ engagement is within reach with the introduction of Blue Ocean Leadership that provides a totally new approach as employees views are taken into consideration in developing new leadership profile. What makes it more interesting, it can be implemented at any time, low cost and able to provide high impact result. The issue of employee engagement needs special attention as the current situation portrays a shocking truth where only 13% of employees worldwide are engaged. In Malaysia, the rate is even worse as there are only 11% employees engaged in their jobs. Hence, employee engagement is critical issue that need to be addressed urgently in public service. As such, Blue Ocean Leadership is offering new framework and tools for leaders in public service with the aim of increasing level of employee engagement. Finally, this new leadership profile is shown on leadership canvas and shared among employees that aim to motivate them to strive for organizational excellence.